Flow effects on the surface properties of surfactant foam films. Issue 47 (30th November 2021) - Ye, Zhicheng; Yang, Jie; Su, Haiping; Lian, Cheng; Shang, Yazhuo; Liu, Honglai
Abstract : The pressure-induced liquid flow affects the surface electrostatic properties of liquid foam. Abstract : The surface electrostatic properties of liquid foam, involving the electrokinetic (EK) phenomena in the liquid–gas interface, have significant effects on the stability of the foam. Here, we established a theoretical model for ion transport in liquid films by combining the liquid flow and surface reaction. We found that the surface electrostatic properties of liquid foams were influenced unexpectedly by the pressure-induced flow. The liquid flow will induce the potential and concentration differences in the flow direction. When the pressure drop increases to a certain high value, the induced potential and salt concentration difference increases, leading to the change of the surface electrostatic properties such as zeta potential and the surface charge density. This change shows that the surface electrostatic properties of foam films depend on the coupling of various factors including ion distribution and pressure drop, which deepens our understanding of the electrostatic properties of the foam films.